Successful turnaround strategy: Thailand evidence - Evans, Robert; Chitnomrath, Thanida; Christopher, Theo (Emerald Group Publishing Ltd., 2013)
Purpose – This research seeks to determine the success of turnaround strategies adopted by corporations in Thailand following post-bankruptcy reorganization plans approved by the Thai Central Bankruptcy Court. Design/methodology/approach – The study uses a sample of 101 companies whose reorganization plans have been confirmed by the Thai Central Bankruptcy Court in the period 1999-2002, with performance measures to 2005. Findings – The results indicate that over a three-year reorganization period successful companies were found to be most likely to adopt cost and expense reduction, company size reduction and disposal of non-core assets while operational strategies aimed at reconfiguring internal operations and systems were not likely to be associated with successful companies. Practical implications – The data suggests, subject to limitations, the selection of restructuring methods may differ between those companies which successfully reform and those which do not. Companies pursuing successful turnaround strategies were found most likely to adopt cost and expense reduction, company size reduction and disposal of non-core assets as significant operational strategy. Originality/value – Prior research in Thailand has not investigated turnaround strategy of successful and unsuccessful companies. The result of the study has practical significance as it provides information of use to regulators, management, lenders, creditors, practitioners, and investors. The prevailing economic conditions worldwide suggest the need for replication and continual refinement of research in this area, not only in Thailand but elsewhere.